A Comparative Analysis of Early Childhood Care and Education (ECCE) Policies: Malaysia and Selected International Contexts - Mohd Zuri Ghani; Erina Asmawani Abu Bakar; Noorzazila abdul manaf; Nur Sakina Mokhtar; Cynthia saineh; Komalah Appu (SEA-CECCEP, 2025)
This study conducts a systematic literature review (SLR) to compare early childhood care and education (ECCE) policy frameworks between Malaysia and four selected countries: Sweden, New Zealand, Australia, and Japan. The objective is to identify key policy elements that can inform the enhancement of Malaysia’s ECCE system, particularly in the areas of policy integration and the professionalization of ECCE educators. A total of 712 articles were initially retrieved through major academic databases. After applying inclusion and exclusion criteria, 41 relevant articles were selected for in-depth analysis. The selected countries were chosen based on their exemplary ECCE systems, international rankings, and relevance to Malaysia’s policy aspirations ranging from structural similarities in public-private partnerships (e.g., Australia and New Zealand) to high-quality and publicly funded models (e.g., Sweden and Japan). Thematic analysis was employed to examine five major themes: curriculum and pedagogy, educator qualification standards, governance and accountability, access and equity, and cultural responsiveness. The findings reveal both unique and overlapping policy strategies, with emphasis on the role of integrated governance, continuous professional development, and culturally contextualized curricula. Malaysia stands to benefit from adapting international best practices in ways that suit its local sociocultural and administrative frameworks. The study also discusses the limitations of using secondary data and calls for more empirical, field-based studies in future research. This comparative approach contributes to a better understanding of how global ECCE policy trends can be translated into meaningful reforms within the Malaysian context.